Valensuppgifter i finska inlärningsordböcker – en oknäckt nöt - Martola, Nina; Grönros, Eija-Riitta (Nordiske Studier i Leksikografi, 2010)
In the last years the immigration to Finland has increased and, as a consequence of that, the need for L2-dictionaries of Finnish. For small languages like Finnish, however, it is sensible to take into consideration also the needs of other L2-learners than immigrants, since separate dictionaries for different learner groups is hardly a realistic thought. But that increases the challenges for the dictionary makers. The question of how to represent valencies for the entries is always problematic but for Finnish you are additionally facing the fact that syntactical and aspectual matters have great impact on how the lexical valency turn out in use. In this article we present some of the problems you are faced with as a learner and as a dictionary maker and we also discuss possibilities of solving some of the problems.